Why Kiswahili adopted the words for six, seven and nine.pdf - Aimee Johansen (LibraryPress@UF, 2003)
This squib addresses the topic of the numeral system of Kiswahili, in which some numerals are of Bantu origin and others are borrowed from Arabic. The main issue of interest is the following: Why did Kiswahili adopt the Arabic words for 'six', 'seven' and 'nine', when Kiswahili words already existed for these numerals? Little has been written on this topic, other than simple descriptions of the facts. I argue that sita 'six' and saba 'seven' were borrowed to replace the existing Bantu forms because they fit better into the pattern of disyllabic words found in the Kiswahili numbers from 1 to 10. The word for 'eight' was not borrowed because the Bantu word already fit this pattern. I also demonstrate that tisa 'nine' was borrowed into the language later than sita and saba, and probably for different reasons.